Professional Self Efficacy Scale for Information and Computer Technology Teachers Validity and Reliability Study - Yıldız, Rauf; Banoğlu, Köksal; Ruben, Vanderline (My University, 2015)
This study aims at developing a valid and reliable scale to measure information and communication technology (ICT) teachers’ self-efficacy related to the Turkish national framework of ICT competencies. For statistical procedures, data were respectively analyzed with exploratory factor analysis (EFA) and confirmatory factor analysis (CFA). Furthermore, test-retest procedure was carried out to confirm the time invariance of the scale. EFA results revealed that the scale’s seven-factor structure accounts for 65.90 percent of total variance. CFA results produced an acceptable statistical support for model-data fit between the observed item scores and the seven-dimension scale structure (X2 /df= 1.98, RMSEA= .073, CFI= .86). The standardized regression weights between the latent and observed variables ranged from .57 to .89 and Cronbach’s alpha coefficient of the scale subdimensions ranged from .80 to .88. Besides, the item-scale correlations varied between values of .53 and .79. As a result, the developed scale is a likert questionnaire and composed of 33 five-point items with seven sub-dimensions.
Keywords: Teacher Self-efficacy; ICT Competency; ICT Framework; Technology Leadership; Scale Development